Relationship between personality traits and perinatal depression at Muhammadiyah Hospital Surabaya - Ninuk Dwi Ariningtyas; Putri Aqila; Era Catur Prasetya; Roni Subagyo (Qanun Medika - Jurnal Kedokteran FK UMSurabaya, 2023)
Perinatal depression is a feeling disorder that occurs in a woman during pregnancy and after childbirth. Perinatal depression can be seen from various factors, one of which is personality traits. This study aims to determine the relationship of personality traits with perinatal depression at Muhammadiyah Hospital Surabaya. This study was observative analytic using a cross-sectional approach, conducted on 96 respondents using the Edinburgh Postnatal Depression Scale (EPDS) and the OCEAN personality trait questionnaire. The result of the multiple linear statistical tests on the F test is p=0.00 (p<0.05), the t-test on the extraversion personality trait is p=0.031 (p<0.05), and the neuroticism personality trait is p=0.000 (p<0.05). The coefficient of determination test R2= 37.0%. In conclusion, there is a relationship between personality traits and perinatal depression at Muhammadiyah Surabaya Hospital.